Common colonic community indicators of the suckling pig microbiota where diversity and abundance correlate with performance. Issue 5 (2nd May 2022) - Lee, Adam; Le Bon, Melanie; Connerton, Ian F; Mellits, Kenneth H
Abstract: The primary objective of this study was to investigate if common colonic community indicators could be identified from the microbiota of 22-day-old suckling pigs in repeated small-scale trials. A total of three separate trials were conducted at different times in the same year and facility with genetically similar animals. Colonic samples were collected from four pigs in each trial and the microbiome composition assessed by 16s rRNA gene sequencing. Pig weight, average daily gain (ADG), bacterial diversity, and abundance were not significantly different between repeated trials, except for a significant difference in Jaccard Similarity. At genus level, the most abundant taxa identified were Porphyromonadaceae unclassified (15.81%), Ruminococcaceae unclassified, (12.78%), Prevotella (7.26%), Clostridiales unclassified (6.99%), Lactobacillus (6.58%), Phascolarctobacterium (6.52%), and Firmicutes unclassified (5.69%). The secondary objective was to establish if pooled data in terms of microbial diversity and abundance of the colonic microbiota related to weight and ADG. Pig weight at day 22 and ADG positively correlated with α-diversity. Abundance of potential protein digesting and short-chain fatty acid producing operational taxonomic units ascribed to Terrisporobacter, Ruminococcaceae unclassified, Intestinimonas, and Dorea correlated with weight and ADG, suggesting a nutritional role for these common colonic community microbiota members in suckling pigs. Abstract : Common colonic community indicators can be identified from suckling pigs in repeated trials without major significant differences in diversity, abundance, or microbiota composition.